Research progress on the spatiotemporal dynamics of therapy-induced senescence in remodeling the tumor microenvironment - Zhao, Qingqing; Yu, Yunyan; Pu, Chaorui; Zheng, Shujuan; Chen, Lin; Zeng, Feng; Liu, Li; Li, Dan (Frontiers in Immunology, 2026)
This review systematically elaborates on the spatiotemporal dynamics and dual role of Therapy-Induced Senescence (TIS) in remodeling the Tumor Microenvironment (TME). The hallmark of TIS is the Senescence-Associated Secretory Phenotype (SASP), which drives multidimensional TME reprogramming through the secretion of various factors. These effects include the activation of Cancer-Associated Fibroblasts (CAFs), promotion of Vasculogenic Mimicry (VM), induction of metabolic reprogramming, and bidirectional regulation of the immune landscape. The article provides a focused analysis of the heterogeneous manifestations of this dual effect across different treatment stage and spatial locations, highlighting the definition of the threshold between its tumor-suppressive and tumor-promoting functions as a central current challenge. Finally, it explores future strategies involving multi-omics dynamic monitoring, artificial intelligence analysis, and spatiotemporally specific targeted interventions. In summary, this review aims to provide a theoretical foundation and translational directions for developing novel combination therapies targeting the senescent microenvironment by offering an in-depth analysis of the spatiotemporal dynamics of TIS.